Surface Tuning of La0.5Sr0.5CoO3 Perovskite Catalysts by Acetic Acid for NOx Storage and Reduction - Peng, Yue; Si, Wenzhe; Luo, Jinming; Su, Wenkang; Chang, Huazhen; Li, Junhua; Hao, Jiming; Crittenden, John (Environmental science & technology, 2016)
Selective dissolution of perovskite A site (A of ABO3 structure) was performed on the La1 - xSrxCoO3 catalysts for the NOx storage and reduction (NSR) reaction. The surface area of the catalysts were enhanced using dilute HNO3 impregnation to dissolve Sr. Inactive SrCO3 was removed effectively within 6 h, and the catalyst preserved the perovskite framework after 24 h of treatment. The tuned catalysts exhibited higher NSR performance (both NOx storage and NO-to-NO2 oxidation) under lean-burn and fuel-rich cycles at 250 °C. Large amounts of NOx adsorption were due to the increase of nitrate/nitrite species bonding to the A site and the growth of newly formed monodentate nitrate species. Nitrate species were stored stably on the partial exposed Sr(2+) cations. These exposed Sr(2+) cations played an important role on the NOx reduction by C3H6. High NO-to-NO2 oxidation ability was due to the generation of oxygen defects and Co(2+)-Co(3+) redox couples, which resulted from B-site exsolution induced by A-site dissolution. Hence, our method is facile to modify the surface structures of perovskite catalysts and provides a new strategy to obtain highly active catalysts for the NSR reaction.